Analysis of Leadership Style at Sukasari Village Office Sumedang - Rizal Giovanni Nugraha; Kisthi Hanila Dewi; Thessa Izfadllillah (Journal of Bussines Management Basic, 2022)
Leadership is a process in influencing the activities of a person or group in an effort to achieve goals in certain situations. In Sukasari Village, Sumedang often employees (HR) who arrive late and do not work effectively as needed, appropriate leadership is needed in their employee duties to be more effective in carrying out and responsibilities, based on this, it is effective to know what leadership style is used and a way so that employees can come on time and work well in Suksari Sumedang Village. This research was conducted with a descriptive qualitative research method approach. Sampling was done by purposive sampling technique, as the object of this research was the village head in Sukasari Village, Sumedang. Data collection techniques through observation, online interviews and documentation. Research data were analyzed using miles and hubermen which included data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the leadership style applied in Suksari Sumedang Village is more dominant in the democratic leadership style. Which in practice the leader implements the decisions made with the leader and subordinates, are free to express opinions so that subordinates can also work together in finding good solutions to the problems at hand.